Implementasi Strategi KOL Marketing pada Kampanye Digital Elsheskin - Ramdani, Ratu Chiandita Meidinah; Bachtiar, Willy (Medium: Jurnal Ilmiah Fakultas Ilmu Komunikasi, 2026)
This study examines the implementation and effectiveness of Key Opinion Leader (KOL) Marketing in increasing awareness of Elsheskin’s digital campaign. This topic was selected because KOL-driven strategies have become increasingly influential in shaping consumer decisions, particularly within the highly competitive beauty industry driven by social-media trends. A descriptive qualitative method was employed, with data collected through observation, interviews, participation, and document analysis during a six-month internship. The findings show that KOL Marketing was carried out through structured planning and implementation stages, including KOL selection, trend-based brief development, product distribution, and performance monitoring. The application of Integrated Marketing Communication (IMC) principles such as consistency, complementarity, customer-centricity, cross-functional planning, and measurement supported message alignment across digital channels. The campaign resulted in 492 TikTok uploads reaching 383,201 users and 487 Instagram Reels reaching 325,365 users, supported by efficient CPV values (IDR 57.18 and IDR 67.34). These findings demonstrate that KOL Marketing plays a significant role in enhancing Elsheskin’s brand awareness and serves as a relevant strategic approach for optimizing digital campaign performance. Keywords: Integrated Marketing Communication, KOL Marketing, KOL Specialist